PENGARUH FORMULASI BIOCHAR DAN LIMBAH KULIT KOPI TERHADAP PERTUMBUHAN BIBIT KOPI - Fitri Yelli; Hanisah Hanisah; Rusdi Evizal; Sugiatno Sugiatno (Universitas Lampung, 2020)
Coffee husk is the main waste of coffee bean production using a dry processing system. Coffee husk is returned to the coffee plantation as mulch, or used as a mixture for nursery media and for making bio-charcoal. This study aims to determine the effect of the formulation of biochar, coffee husk, and soil on the growth of Arabica coffee seedlings. The experiment used a randomized block design (RBD) consisting of 6 treatments with 4 replications. The treatments were the composition of the ratio of biochar: coffee husk: soil (v / v / v), namely: 0: 1: 2 (control, without biochar), 1: 1: 2, 1: 0: 2 (without coffee skin), 2: 1: 2, 1: 2: 2, and 1: 1: 1. The coffee husk biochar is made by a slow burning system in a stack. The results showed that: (1) The treatment of biochar composition, coffee husk and soil had an effect on the number of leaves, length x leaf width, crown dry weight, fresh weight quality index, and dry weight quality index; (2) biochar mixing treatment did not increase seedling growth. Mixing biochar with a composition of 1: 1: 2 reduces root growth; (3) the composition of biochar, coffee husk and soil 1: 1: 2 gave better seedling growth than the composition 0: 1: 2 (control without biochar) based on the quality index of fresh seedling and dry seedling.Keywords: Arabica, biochar, coffee husk, growth, seedling, quality indeces